A vallási hovatartozás generációk közti változása néhány kisebb egyház tagságánál - Máté-Tóth András (Vallás a társadalomban = Religion in society, 2008)
The stability or change of religious affiliation among generations is one of the most interesting questions of the sociology of religion. International publications of this topic can be categorized into three groups according to their subjects. However, belonging to one group is naturally not exclusive, thus a certain publication may not deal with only one set of questions as we will see in our short review. The first set of questions deals with the general characteristics of religious tendencies and their cause, demographical indicators, especially denominational specialties. Publications dealing with the religiousness and denominational switching of adolescents have to be put into a different category. The third topic of international publications is undoubtedly the so called brainwash theory. However, the detailed examination of this last category is beyond the limits of this study.